Dimerization of a copper(II) compound with a tetradentate diaminodiamide ligand - Comba, Peter (Dalton transactions, 1999)
Two types of crystals were isolated from aqueous solutions of copper(II) salts, the tetradentate diaminodiamide ligand H2L1 (H2L1 = 1,8-diamino-3,6-diazaoctane-4,5-dione) and base. Crystal structural analyses revealed that one is the expected [Cu(L1)] and the other is the corresponding dimer [Cu2(L1)2], with the two copper(II) chromophores in nearly parallel planes (Cu· · ·Cu distance = 3.35 Å; angle between the two planes, θ = 18.6°), where each ligand co-ordinates to both metal centers. Relief of strain, induced by the central, flat, five-membered chelate ring with two amide donors and two fused five-membered rings, and van der Waals attractions may be responsible for the stabilization of the dimer. This is supported by force field calculations which accurately reproduce the experimentally observed structures (RMS = 0.14 (monomer), 0.19 Å (dimer)), define them as the lowest strain energy conformers and find a stabilization of the dimer by 24 kJ mol-1 (ΔUstrain = 2Ustrainmonomer - Ustraindimer).